Overview Terhadap Faktor Yang Mempengaruhi Implementasi Pengembangan Pariwisata Di Kepulauan Anambas - Etika Khairina; Renita Kurnia; Diki Zukriadi; M. Andika Surya Lebang; Padrisan Jamba (Prosiding, 2023)
This research aims to analyze the factors that influence the implementation of tourism development in the Anambas Islands to increase the number of tourist visits. The research method is descriptive qualitative, primary data sources are interviews and observations. Secondary resources are reviews of relevant literature and documentation from the Anambas Cultural Tourism Office. The data analysis technique is Triangulation. Factors influencing implementation can be seen from the theory developed by Van Metter and Van Horn, namely policy standards and targets, resources, communication, characteristics of implementing agents, and social, political, and economic conditions. The regulations governing Anambas Islands tourism are included in the National Tourism Destination (DPN) development plan through the 2010-2025 National Tourism Development Master Plan (RIPPARNAS), which is directed at tourism development which is difficult to achieve policy program targets, this is because in the regulations There are no Standard Operating Procedures available in tourism development itself, so that SOPs in regulations become one of the influential obstacles. Then, synergy between the government and the community is needed in implementing the tourism development of the Anambas Islands.